Spherical Accretion in the Schwarzschild Spacetime in the Newtonian Analogous Construct - Shubhrangshu Ghosh; Souvik Ghose; Kalyanbrata Pal; Arunabha Bhadra; Tapas K. Das (The Astrophysical Journal)
The velocity-dependent Newtonian analogous potentials (NAPs) corresponding to general relativistic (GR) spacetimes accurately capture most of the relativistic features, including all classical tests of GR, effectively representing spacetime geometries in Newtonian terms. The NAP formulated by Tejeda & Rosswog (TR13) for Schwarzschild spacetime has been applied to the standard thin accretion disk around a black hole (BH) as well as in the context of streamlines of noninteracting particles accreting onto a Schwarzschild BH, showing good agreement with the exact relativistic solutions. As a further application, here we explore the extent to which TR13 NAP could describe a transonic hydrodynamical spherical accretion flow in Schwarzschild spacetime within the framework of standard Newtonian hydrodynamics. Instead of obtaining a typical single “saddle-type” sonic transition, a “saddle–spiral pair” is produced, with the inner sonic point being an (unphysical) “spiral type” and the outer being a usual “saddle type.” The Bondi accretion rate at outer sonic radii, however, remains consistent with that of the GR case. The primary reason for the deviation of our findings from the classical Bondi solution is likely due to the inconsistency between the Euler-type equation in the presence of velocity-dependent TR13 NAP within the standard Newtonian hydrodynamics framework, and the corresponding GR Euler equation, regardless of the fluid’s energy. Our study suggests that a (modified) hydrodynamical formalism is needed to effectively implement such potentials in transonic accretion studies that align with the spirit of TR13 like NAP, while remaining consistent with the GR hydrodynamics. This could then essentially circumvent GR hydrodynamics or GR magnetohydrodynamics equations